Corticoid-like anti-inflammatory effect of Vochysia bifalcata Warm.: Preclinical evidence of efficacy and safety. (24th April 2020) - Horinouchi, Cintia Delai da Silva; Soley, Bruna da Silva; Mendes, Daniel Augusto Gasparin Bueno; Ferreira, Bárbara Guerreira Alpande; Meyre-Silva, Christiane; Farias, Ingrid Vicente; Krueger, Clarissa de Medeiros Amorim; Bresolin, Tania Mari Bellé; Assreuy, Jamil; Zuffellato-Ribas, Katia Christina; Cabrini, Daniela Almeida; Otuki, Michel Fleith
Abstract: Ethnopharmacological relevance: Vochysia bifalcata is a Brazilian native tree commonly used for economic purpose in the reforestation and in the manufacture of products. However, the potential usage of other parts of the plant is usually wasted. Besides, other species of Vochysia are well known for its anti-inflammatory action. Aim of the study: In this study we evaluate the possible anti-inflammatory activity of the hydroethanolic extract from the leaves of V. bifalcata in models of mice skin inflammation. Materials and methods: Effects of V. bifalcata were evaluated in croton oil-induced acute and chronic skin inflammation. The role of glucocorticoid receptors in the extract effect was assessed by using a glucocorticoid receptor antagonist and by a specific binding assay. Possible adverse effects were evaluated after multiple treatments with the extract in a skin atrophy model. Results: Topical application of V. bifalcata reduced ear edema formation, cell infiltration and interleukin (IL)-6 and tumor necrosis factor (TNF)-α levels. In the chronic model, besides edema formation and cell infiltration, the extract inhibited epidermal hyperproliferation and Proliferating Cell Nuclear Antigen expression. V. bifalcata seems to act by biding to corticoid receptors, however it did not induce corticoid related undesirable effects. Conclusion: Hydroethanolic extract from leaves of V. bifalcata could be an interesting tool in the search for new anti-inflammatory and antiproliferative agents for the treatment of skin disorders. Graphical abstract: Image 1